Analisis Kemampuan Mahasiswa Fisika Menggunakan Multimeter Analog Dalam Praktikum Elektronika Analog - Aura Fatima; Yessy Umi Salma; Windy Atika Sari; Pujianto; Bayu Setiaji (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
The ability of physics students related to the use of multimeters in practicum is still invaluable. This results in the data of practicum conducted by students. This study aims to determine the ability of physics students in the use of multimeters. The research method used is a quantitative method using an observation questionnaire when the practicum is carried out for one semester. The research was conducted on students of the physics study program in 2nd semester. In the use of multimeters as ohm meters, there are 46.66% of groups that have done the first step, 40% of the groups have done the second step, and 73.33% of the groups have done the third step. Then, in the use of multimeters as ammeters, 40% of the group has done the first step, 53.33% of the group has done the second step, and 73.33% of the group has done the third step. Meanwhile, in the use of multimeters as voltmeters, 40% of the group has done the first step, 46.66% of the group has done the second step, and 66.66% of the group has done the third step. The results of this study show that most students still go through several steps that need to be taken in the use of analog multimeters, starting from their use as ohmmeters, ammeters, to voltmeters.